Implementation of Content and Language Integrated Learning (CLIL) in Teaching English for Guiding - Made Aryawan Adijaya (Journal for Lesson and Learning Studies, 2023)
In the globalization era, students are led to be able to have the interaction between countries and cultures. It causes the students to be proficient at using English as a communication tool. Besides, it is also used to compete globally. Therefore, this research aims to analyse content and language integrated learning (CLIL) implementation in English for Guiding of Diploma 3 of English Department. The data were gathered by documents study of the curriculum of study program, syllabus, and semester lesson plan of the course. This study used a qualitative approach on the basis of a qualitative study or an interpretive research design. Qualitative research is research that has the goal of analyzing data, especially the formation of new views that require the perspective of the respondent. The result found that the curriculum has explicitely stated that the students are expected to be able to use English in the area of tourism. It means both English proficiency and contents in tourism are obligatory delivered to the students. However, the syllabus and semester lesson plan give more emphasis on the students’ mastery on English with less attention given to the contents of tourism.